Money laundering and terrorist finance - Passas, Nikos (Henry Stewart Talks, 2008)
Stages of money laundering, What is the problem?, Financial institution risks, Problem of non-AML action, Terrorism finance, Extent and volume, Means and methods, Under invoicing, Cigarettes without diversion, Undervalued timber export, Diamond import, La Mina and gold, Hawala and over-invoiced exports, Objectives of AML, International standards, The Financial Action Task Force, Counter-financing of terrorism, International cooperation, What do we know about criminal funds?, Tasks for countries, regulators and the private sector